The β-subunit of G proteins is a substrate of protein histidine phosphatase - Mäurer, Anette; Wieland, Thomas; Meissl, Florian; Niroomand, Feraydoon; Mehringer, Rebecca; Krieglstein, Josef; Klumpp, Susanne (Biochemical and biophysical research communications, 2005)
Increasing evidence suggests that reversible phosphorylation of histidine residues in proteins is important for signaling cascades in eukaryotic cells. Recently, the first eukaryotic protein histidine phosphatase (PHP) was identified. The beta1-subunit of heterotrimeric G proteins (Gbeta) undergoes phosphorylation on His266 which is apparently involved in receptor-independent G protein activation. We studied whether phosphorylated Gbeta-subunits are substrates of PHP. Phosphorylated Gbetagamma dimers of the retinal G protein transducin and Gbeta in membrane preparations of H10 cells (neonatal rat cardiomyocytes) were dephosphorylated by PHP. Overexpression of PHP in H10 cells showed that PHP and Gbeta also interfere within cells. In membranes of cells overexpressing PHP, the amount of phosphorylated Gbeta was largely reduced. Both our in vitro and cell studies indicate that phosphorylated Gbeta-subunits of heterotrimeric G proteins are substrates of PHP. Therefore, PHP might play a role in the regulation of signal transduction via heterotrimeric G proteins.